2021
DOI: 10.1007/s40430-020-02777-6
|View full text |Cite
|
Sign up to set email alerts
|

Current challenges in modelling vibrational fatigue and fracture of structures: a review

Abstract: Fatigue damage is a concern in the engineering applications particularly for metal structures. The design phase of a structure considers factors that can prevent or delay the fatigue and fracture failures and increase its working life. This paper compiled some of the past efforts to share the modelling challenges. It provides an overview on the existing research complexities in the area of fatigue and fracture modelling. This paper reviews the previous research work under five prominent challenges: assessing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 187 publications
(261 reference statements)
0
12
0
Order By: Relevance
“…It was also found that the interatomic bond length increases with increasing temperatures [23]. Recent review papers on the dynamic response of the system at elevated temperatures can be found in the literature [1,2,[30][31][32][33].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…It was also found that the interatomic bond length increases with increasing temperatures [23]. Recent review papers on the dynamic response of the system at elevated temperatures can be found in the literature [1,2,[30][31][32][33].…”
Section: Introductionmentioning
confidence: 93%
“…Researchers considered that early detection is the solution to prevent catastrophic damage. Modal analysis is one of the common techniques used to study structure health monitoring [1][2][3]. This paper aims to study the modal and crack propagation behavior of a beam subjected to thermal and mechanical loads.…”
Section: Introductionmentioning
confidence: 99%
“…However, only tensile stress was responsible for the propagation of the crack. Therefore, the stress amplitude σ i (l c ) was used to show the stress range per cycle instead of the difference among the peak and trough as shown in Equation (12). After that, the bending moment 𝑀 (𝑙 ) at the crack location in i th cycle can be calculated by Equation (10):…”
Section: Calculation Of Sif Range and Fcg Ratementioning
confidence: 99%
“…These structures can experience fatigue failure due to dynamic loads in a complex thermo-mechanical environment [10][11][12]. Compared with other materials [13][14][15][16][17], the crack propagation during fatigue is highly complicated for FDM polymeric structures because of the significant differences in its microstructure due to various printing parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Vibration-based inspection of mechanical structures for structural health monitoring is widely studied [1][2][3]. However, many engineering practical applications such as automotive, aircraft, power plants, etc.…”
Section: Introductionmentioning
confidence: 99%